Manajemen Risiko Berbasis Maqasid Syariah Sebagai Strategi Keberlanjutan Bank Syariah Di Indonesia: Kajian Literatur - Dewi Risyantika; Laili Fathul Hidayah; Reska Maulida; Riyan Damara Putra; Ridwansyah Ridwansyah; Wan Ruslan Abdul Ghani (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to systematically review the integration of maqasid al-shariah into Islamic bank risk management and to develop a conceptual framework linking Shariah values, risk categories, governance, and sustainability. The study employs a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Data were collected from Scopus, Web of Science, and Google Scholar using combinations of the keywords